The bazaar of bad dreams : stories - King, Stephen, 1947-; Baker, Dylan; Bloom, Brooke; Chalfant, Kathleen, 1945-; Davis, Hope, 1967-; Fontana, Santino; Friedman, Peter, 1949-; Graham, Holter; Herrmann, Edward, 1943-2014; Patton, Will; King, Stephen, 1947-; King, Stephen, 1947-; et al. (New York, NY : Audioworks, Simon & Schuster Audio, 2015)
Presents a collection of twenty recent short stories, accompanied by commentary on each piece's themes and origins.
Title from container.
Read by the author, Dylan Baker, Brooke Bloom, Kathleen Chalfant, Hope Davis, Santino Fontana, Peter Friedman, Holter Graham, Edward Herrmann, Will Patton [and 6 others].
Keywords: Suspense fiction; Horror fiction; Short stories; Audiobooks